Secular Stagnation: Is Immigration Part of the Solution? - José Alves; Sandro Morgado (Center for Economic Studies and ifo Institute (CESifo), 2022)
In our article we review the secular stagnation hypothesis, firstly postulated by Hansen (1939), to describe the current macroeconomic dynamics faced by developed economies. Based in the existing literature, we elaborate on a workable definition of secular stagnation founded on four pillars: diminished long run growth potential, increasing aggregate demand shortages, lowering of nominal short term interest rates and increasingly immovable unemployment. This four-pillar definition reveals a fundamental problematic faced by these economies; while a diminished long run growth potential, increasing aggregate demand shortages and an increasingly immovable unemployment stress the need for full employment policy measures, the lowering of nominal short term interest rates makes the mostly resorted to full employment policy measure, in the form of expansionary monetary policy, ineffective. This problematic implies an imperative rethinking of the policy framework in times of secular stagnation. For that, we consider one of the most evoked factors causing secular stagnation, demographics in the form of an aging population and a declining working age population, hence highlighting the pertinence of immigration as a possible solution. We do so by empirically observing the pillars of secular stagnation and testing the impact of demographic factors on those features, resorting to panel data analysis. Focusing on the EU15 and US economies, with data ranging from 1965 to 2020, we conclude that the four pillars we based our definition of secular stagnation upon can be empirically observed and that demographic factors play a statistically significant role for those determining features thus highlighting the pertinence of immigration as a possible solution.
Keywords: E52; G01; J11; O47; 330; economic stagnation; secular stagnation; financial crisis; immigration; monetary policy